“An Endless Cycle of Worry and Hardship”: The Impact of COVID-19 on the Food Security of Somali Migrants and Refugees in Nairobi, Kenya (African Human Mobility Review, 2025)
COVID-19 has produced unprecedented effects on the global economy and society by exposing multiple weaknesses and faultiness. The pandemic has disrupted global and local agricultural production processes and food supply chains with negative consequences for food security. Containment measures to limit the spread of COVID-19, including strict restrictions on the movement of people, goods, and services have affected urban food systems adversely in multiple ways. Urban migrants and refugees in many parts of the Global South have been disproportionately hit by these measures, increasing the precarity of their living conditions and exacerbating the food insecurity of the migrants’ households. Based on the results of a household survey and in-depth interviews with Somali migrants in Nairobi, Kenya in August 2022, this study documents the pandemic-related experience of these migrants in food access and consumption and assesses the overall impacts of COVID-19 on their food security. This study seeks to contribute to the emerging body of case study evidence that assesses the food security outcomes of the pandemic in vulnerable populations.